STRATEGI MENCIPTAKAN, MEMPERTAHANKAN DAN MENJUAL PERSONAL BRANDING JELANG PEMILU 2014 - Bambang Joko Priyono (Universitas Mercu Buana, 2014)
The purpose of this paper is made to describe some of the definitions of PersonalBranding from various sources. So it is expected to increase our understanding and theknowledge about Personal Branding. Because to know how a character creation process, orbetter known as the Personal Image or Personal Branding is not something so difficult.Creating it is easy, but how to manage and maintain a self branding that has made it moredifficult. Discussion of the results obtained to the fact that the Personal Branding is theimage of the person that was built by the person concerned and appreciated by peoplearound him. Perhaps in simple language Personal Branding can be defined as